Pesticide susceptibility monitoring of fall armyworms (Spodoptera frugiperda (J.E. Smith)): a simple methodology for information-sharing among Southeast Asian countries - Supangkana Thirawut; Woravit Sutjaritthammajariyangkun; Artit Rukkasikorn; Pruetthichat Punyawattoe; Uraporn Noonart; Youichi Kobori (CABI Agriculture and Bioscience)
Abstract Background The fall armyworm, Spodoptera frugiperda, is a destructive moth pest. It is highly migratory and was first detected in Southeast Asia in 2018, rapidly becoming a major pest of corn production in this region. Monitoring the susceptibility of S. frugiperda populations is important for efficient insecticide resistance management. Because of the high mobility of this pest, information-sharing of susceptibility levels among neighboring countries is required for insecticide resistance management. To this end, we developed simple standard methods for pesticide susceptibility monitoring of S. frugiperda to contribute to information-sharing among Southeast Asian countries. Methods The developed methods included mass rearing of larvae using an artificial diet and bioassay by diet overlay. The lethal concentrations for 50% and 95% mortality (LC50 and LC95) and resistance coefficient values were calculated. We tested the susceptibilities of samples of S. frugiperda collected from the six major corn planting areas in Thailand to emamectin benzoate, spinetoram, chlorantraniliprole, indoxacarb, chlorfenapyr, and lufenuron using the developed methods. Results The mortality of artificial diet-fed larvae was higher than those fed corn leaves, especially in the early instars. However, more than half of the specimens reared on the artificial diet became pupae. In the case of three of the six pesticides, emamectin benzoate, indoxacarb, and chlorfenapyr, the LC50 values of the samples collected in 2021 and 2022 were significantly higher than those collected in 2019, indicating increasing resistance to those three pesticides. According to the resistance coefficient values, only samples from one area exhibited low resistance to lufenuron. Conclusions We developed a simple standardized methodology for Southeast Asian countries to compare insecticide susceptibility. The calculated LC50 and resistance coefficient values can be used as a baseline for monitoring the development of pesticide resistance in the region. The LC50 values of several pesticides have increased significantly over the years. However, the resistance coefficient values indicated that S. frugiperda developed low resistance to only one pesticide (lufenuron). This study offers helpful information for insecticide selection and improved resistance management of fall armyworms in Thailand.